Development and Validation of an Administrative Codes Algorithm to Identify Abdominal Surgery and Bowel Obstruction in Patients With Inflammatory Bowel Disease. Issue 1 (25th February 2021) - Gandle, Cassandra; Scott, Frank I; Waljee, Akbar; Vajravelu, Ravy K; Sansgiry, Shubhada; Hou, Jason K
Abstract: Background: Validated administrative codes (CPT and ICD) can permit the use of large databases to study diseases and outcomes. The aim of this study was to validate administrative codes for surgery and obstructive complications in patients with inflammatory bowel disease (IBD). Methods: We performed a retrospective study of IBD patients within the Veterans Affairs Health Administration (VA) from 2000 to 2015 with administrative codes for bowel surgery and complications validated by chart review. Positive predictive values (PPVs) and negative predictive value (NPV) were calculated. Results: The PPV for bowel surgery was 96.4%; PPV of obstruction codes for bowel obstruction was 80.5% (95% confidence interval: 69.1%, 89.2%). Conclusions: CPT and ICD codes for abdominal surgery and obstructive complications can be accurately utilized in IBD patients in VA. Lay Summary: We studied patients with inflammatory bowel disease who had surgery and reviewed medical records to confirm accuracy of administrative codes. We found the codes to be accurate in most cases and recommend they can be used in future database studies.